Shear induced diffusion of platelets revisited - Kotsalos, Christos; Raynaud, Franck; Lätt, Jonas; Dutta, Ritabrata; Dubois, Frank; Zouaoui Boudjeltia, Karim; Chopard, Bastien (Frontiers in Physiology, 2022)
The transport of platelets in blood is commonly assumed to obey an advection-diffusion equation with a diffusion constant given by the so-called Zidney-Colton theory. Here we reconsider this hypothesis based on experimental observations and numerical simulations including a fully resolved suspension of red blood cells and platelets subject to a shear. We observe that the transport of platelets perpendicular to the flow can be characterized by a non-trivial distribution of velocities with and exponential decreasing bulk, followed by a power law tail. We conclude that such distribution of velocities leads diffusion of platelets about two order of magnitude higher than predicted by Zidney-Colton theory. We tested this distribution with a minimal stochastic model of platelets deposition to cover space and time scales similar to our experimental results, and confirm that the exponential-powerlaw distribution of velocities results in a coefficient of diffusion significantly larger than predicted by the Zidney-Colton theory.